Disturbance of a laminar air flow caused by differently shaped surgical lights. Issue 3 (6th September 2022) - Hofer, Valeria; Hartmann, Anne; Rotheudt, Hansjörg; Zielke, Benjamin; Kriegel, Martin
Abstract: In operating rooms with unidirectional air flow a wake is formed below the light. The influence of the geometry on the dimension of the wake and the age of air were investigated by means of validated numerical simulations as well as experimental measurements. The vertical dimension of the wake caused by the circular surgical light was 1.08 m in height. With an air-permeable shape, it could be reduced to 0.38 m (brim) to 0.28 m (centre). A more open design increased the dilution within the recirculating area and resulted in a shorter residence time of contaminants.